Aqueous cadmium removal by calcium fluoride sludge - Kwan, Kevin Ka Wing. (2008)
There has been an increasing interest in the ability to immobilize heavy metals from contaminated environment. In this study, the feasibility of using calcium fluoride sludge for aqueous cadmium removal had been investigated. In Singapore, the production of flat display television panel generates calcium fluoride sludge in abundance which is a major waste that has to dispose off in land fill. Cadmium isotherm was studied using batch experiments under different cadmium concentrations and also effects of major parameters controlling cadmium removal such as ionic strength and solution pH were evaluated. Results showed that the capacity of aqueous cadmium immobilization by calcium fluoride sludge was relatively high. The mechanisms are mainly two steps of reactions, the dissolution and the precipitation of hydroxyapatite, which were confirmed by X-ray diffraction (XRD) analysis. Cadmium immobilization efficiency by calcium fluoride sludge increases as ionic strength decreases but remain relatively consistent with solution pH range of 3~8 other than below pH3 which can be explained by zeta potential analysis which shows that the solution is in the negative region only after approximately pH2.5. The total cadmium removal rate is contributed by the precipitation of hydroxyapatite and also the formation of cadmium hydroxyl at high pH. The relatively good capacity of calcium fluoride sludge in the immobilization of aqueous cadmium demonstrated its potential to be a cost effective material and being reused in cadmium contaminated environment remediation.